Ojcostwo Abrahama w świetle tekstów patrystycznych - Basiuk, Maciej (Verbum Vitae, 2011)
Paternity of Abraham was very obvious in the biblical time. Israelites treated him as their father who was chosen by God. They believed next generation would be blessed because of God’s promise for Abraham. Also arising Christianity treated him as a progenitor. But a character of his paternity changed. Christians put an accent of his very strong faith instead of physical aspect of his fatherhood. Fathers’ of the Church teaching came in the same way, although they saw him also as an example of father in the physical aspect.